Study of Teacher's Digital Technology Ability in Online Classroom Management - Rahayu, Hikmawati; Muhammad Mumtaz, Nadhif; Khoiriyah, Siti (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
Teacher TIK competence is the ability of teachers to develop learning by utilizing TIK, such as planning, implementing, and innovating learning. Establishing TIK competence as one of the teacher competencies is a logical consequence of the significant positive influence of TIK on educational activities, especially since the pandemic era. This study aims to determine the awareness and competence of teachers to use digital technology in managing classes in this new average era. This research is fundamental and needs to be done to improve the readiness and mastery of high school teachers in the city of Kendari to use technology and classroom management competencies in the learning process. The method used in this research is a descriptive survey using a quantitative approach. The subjects of this study were 36 sample of teachers at SMA Muhammadiyah Kendari. The results showed that the technology skills of Senior High School teachers were good because the total average score and level of achievement of respondents (LAR) from four indicators of TIK ability (computer/laptop operation, use of computer software, internet, and website usage) had reached 4, 11/82.11%. Although it is in a suitable category, it is still necessary to improve specific skills so that they have a maximum impact on good classroom management and problems solving